QUO VADIS PEKERJA ANAK PADA PERKEBUNAN TEMBAKAU DI KABUPATEN JEMBER - Rosita Indrayati (LKKI Fakultas Syariah dan Hukum Universitas Islam Negeri Ar-Raniry, 2017)
The most significant share of child laborers in the world is in agriculture and plantations, where they do various types of agricultural jobs, ranging from small to medium family farming to large agricultural, plantation or agroindustry businesses. The ILO estimates that more than 132 million girls and boys aged 5-14 years old are involved in planting, harvesting agricultural products, spraying pesticides and raising livestock in rural areas and plantations worldwide. The child labor phenomenon in tobacco plantations in Jember Regency has existed since the Dutch colonial era. Several studies have been conducted concerning child labor in tobacco businesses, such as YPSM (1988), Pusat Analisis Sosial Akatiga Bandung (1994 and 2002), Mahbubah (2003), revealed that the problem of child labor and its influencing factors are the